Prices and quality in urban food retail: Evidence from Addis Ababa - Woldu, Thomas; Abebe, Girum; Lamoot, Indra; Minten, Bart (International Food Policy Research Institute, 2013)
We study food retail in Addis Ababa based on a large survey of food retail outlets selling cereals, fruits and vegetables, and pro-cessed foods. The study shows high variation in quality and prices in the city and an increasing differentiation in food retail markets in recent years.